TOLERANCE: FEATURES AND PROBLEMS OF EVALUATION - M. V. Karmanov; O. A. Mahova (Статистика и экономика, 2018)
In the media and in specialized literature, publications related to attempts to assess the place and role of tolerance in the life of modern society are increasingly encountered. In this connection, a comprehensive scientific analysis of tolerance as an independent and distinctive object of applied research is of great scientific and practical interest. Considering the points of view on the category of "tolerance" gave grounds to believe that there are a number of "white spots" and gaps of methodological nature that do not allow collecting reliable information and identify the main indicators characterizing the state and features of the transformation of tolerance as a social norm reflecting changes in society's value orientations . Tolerance as a characteristic of the moral state of society is a "medal with two sides": on the one hand, it is positive that it promotes mutual understanding, taking into account the recognition of rights and freedoms, with the coordination of different motives, attitudes and orientations without violence and suppression of human dignity, allows to smooth existing irreconcilable interethnic, interethnic, racial contradictions; on the other negative, because it can be perceived as permissiveness, and instill indifference to values. All of the above was justification for the need to present in the article a critical analysis of approaches to the definition and directions of the study of tolerance, which made it possible to reveal its principal features as a complex and multifaceted object of statistical research. In order to implement the principle of objectivity of conclusions, the study was conducted using the following methods: analysis and synthesis, comparison and comparison, generalization, the method of scientific abstraction. The article presents a substantiation of the possibilities of making a quantitative assessment of changes in tolerance in time, taking into account the analysis of information sources, which represent data of predominantly departmental reporting, special sample surveys, and sociological surveys. Evaluation of the information base for the characterization of tolerance has revealed a number of obstacles and difficulties in the way of collecting relevant, complete and accurate statistical information on its development. The authors emphasized the problem of information support of applied research in the field of tolerance, which allowed to formulate a conclusion about the absence and practical impossibility of developing and implementing a universal system of indicators or an integral assessment of tolerance, independent of its kind. The main result of the study was the thesis that there is no single and universally recognized methodology for assessing tolerance, which seems to be a significant obstacle to consolidating the efforts of the state in ensuring national security of the country.